Chiral Separation of Racemic Naproxen by High-Performance Liquid Chromatography with β-CD/SiO2 as the Chiral Stationary Phase. (27th November 2019) - Wang, Lili; Deng, Jian; Ji, Xuezhen; Liu, Wanbin; Liang, Jun; Yan, Xiaona; Chen, Dan; Xie, Jie
Abstract: A novel derivative β-cyclodextrin (β-CD) bonded silica gel (β-CD/SiO2 ) was prepared via carbodiimide activation and used as a chiral stationary phase (CSP). The β-CD/SiO2 CSP was characterizedby X-ray photoelectron spectroscopy and FTIR spectroscopy to prove the successful immobilization of β-CD onto the surface of the silica gel.The thermal behavior of the CSP was studied by differential scanning calorimetry and then used forthe chiral separation of racemic naproxen using HPLC. Several factors affecting the separation efficiency of naproxen enantiomers were investigatedsystematically. The following parameters were selected: methanol–0.01 M phosphate buffer solution (85 + 15, v/v, pH 3.5) was the mobile phase, the flow rate was 1.0 mL/min, and the column temperature was 35°C. Under optimal conditions, the racemic naproxen was efficiently separated with a resolution factor ( R S ) of 1.70 and a separation factor ( α ) of 1.25. This method was successfully used for the enantiomeric separation and purity assessment of naproxen in commercial naproxen sustained release tablets.